Strength of Normal Sections of Flexural Reinforced Concrete Elements Damaged by Corrosion and Strengthened with External Composite Reinforcement - Vladimir I. Rimshin; Lyudmila A. Suleymanova; Pavel A. Amelin (Structural Mechanics of Engineering Constructions and Buildings)
The aim of the study is to develop a methodology for calculating the strength of normal sections of flexural reinforced concrete elements, which suffered corrosion damage and were strengthened with external composite reinforcement. The objects of the study are reinforced concrete elements used in various structures that are exposed to aggressive chloride environment that causes corrosion of concrete and rebars. The research method is based on the use of a diachronic model of deformation of corrosion-damaged elements. This model takes into account changes in the mechanical characteristics of concrete and reinforcement during corrosion and includes equations based on analytical relationships for determining the initial load-bearing capacity of intact structures. An important aspect of the method is taking into account external polymer composite reinforcement, which allows to increase the flexural rigidity and strength characteristics of damaged elements. The Picard’s iterative method, which is designed for approximate solutions of differential equations, was used to ensure the accuracy of calculations. The results of the study showed that the proposed method allows to effectively assess the strength of normal sections of reinforced concrete elements subjected to corrosion. It was found that the methodology, which takes into account the changes in strength and deformation characteristics of materials, as well as the effect of aggressive chloride environment, ensures high accuracy and reliability of the analysis. The use of external polymer composite reinforcement significantly increases the stability and durability of structures. Thus, the developed methodology is an important tool for increasing operational reliability and extending the service life of reinforced concrete structures exposed to aggressive environments, which is a relevant problem in the construction industry.